Cobalt doped graphitic carbon nitride as an effective catalyst for peracetic acid to degrade sulfamethoxazole. Issue 22 (9th May 2022) - Zhou, Runyu; Zhou, Gaofeng; Liu, Yiqing; Wang, Shixiang; Fu, Yongsheng
Abstract : An efficient advanced oxidation process (AOP) for sulfamethoxazole (SMX) removal: peracetic acid activated with cobalt doped graphitic carbon nitride. Abstract : In this study, cobalt doped graphitic carbon nitride (Co–CN) was prepared and applied as a catalyst to activate peracetic acid (PAA) for sulfamethoxazole (SMX) degradation at neutral pH. PAA could be efficiently activated by Co–CN resulting in the efficient degradation of SMX. Characterization results of fresh and used Co–CN suggested that cobalt was successfully doped in graphitic carbon nitride (g-C3 N4 ) through chemical bonding (Co–N bond) and the surface cobalt species in Co–CN ( i.e., Co(ii ) and Co(iii )) were the main activators for PAA. Organic radicals ( i.e., CH3 C(O)O˙ and CH3 C(O)OO˙) were proved to be the dominant reactive species for SMX removal in the Co–CN/PAA system by radical scavenging experiments. The increase of cobalt doping content, PAA dosage or Co–CN dosage could accelerate SMX degradation and the neutral condition was highly favorable to SMX removal in Co–CN/PAA system. Co–CN exhibited a good stability and reusability for PAA activation in degrading SMX. Four possible degradation pathways of SMX ( i.e., hydroxylation, nitration, bond cleavage and coupling reaction) were proposed in the Co–CN/PAA system according to eight identified transformation products.